Pulsed laser deposition of magnesium-containing bioactive glass film on porous Ti–6Al–4V substrate pretreated by micro-arc oxidation. (March 2016) - Ma, J.; Wang, C.Z.; Ban, C.L.; Chen, C.Z.; Zhang, H.M.
Abstract: Commercially pure Ti6Al4V (TC4) was pretreated by micro-arc oxidation (MAO) and then magnesium-containing bioactive glass thin film was successfully grown by pulsed laser deposition (PLD). After MAO and PLD treatments, the effects of MAO pretreatment and surface modification on the film bonding property and bioactivity were evaluated by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM) and scratch tester. The results showed that the deposited film followed the surface relief of the porous MAO coating and strongly bonded to the substrate. And with increased immersion time in simulated body fluid (SBF), the lathlike and spherical apatites were generated and grown, indicating the surface-modified porous Ti6Al4V exhibit good bioactivity. Highlights: Mg-doped glass film was grown on porous Ti6Al4V by pulsed laser deposition. Fine adhesion between the deposited film and the porous substrate was achieved. The apatites were generated and grown on the prepared magnesium-doped glass film. The surface-modified porous Ti6Al4V might be promising candidates as implant.